Can R&D investment reduce the impact of COVID‐19 on firm performance?—Evidence from India. (22nd October 2021) - Biswas, Shreya
Abstract : This study examines whether investing in R&D reduces the impact of exogenous shocks like the COVID‐19 on stock market performance and accounting performance of manufacturing firms in India. For the sample of listed manufacturing firms, the paper finds that the firms engaged in R&D activities had lower negative cumulative abnormal return than those firms that did not invest in R&D in the pre‐pandemic period using multiple event windows. The result suggests that R&D investments can lower value erosion for the shareholders during a severe crisis period. Further, using a difference‐in‐difference fixed effects model, the study finds that manufacturing firms engaged in R&D activities in the pre‐pandemic period exhibited higher return on sales and growth of total income during the pandemic quarter vis‐à‐vis the non‐R&D firms. The favorable accounting performance indicates the possibility of firm‐level R&D being associated with the firm's ability to adjust its functioning during a crisis, thereby reducing the effect of the crisis. Finally, the study documents that government intervention to reduce the spread of the virus had a differential impact on firms based on their industry of operation. The findings have implications for investors, corporate managers, and policymakers in India.